DAMPAK IFLASI DAN NILAI TUKAR RUPIAH TERHADAP KEMISKINAN DAN PENGANGGURAN DI INDONESIA - Edy Supriyadi; Devi Roza Krisnandhi Kausar (Universitas Negeri Makassar, 2016)
The purpose of this research are: (1). Evaluate the impact of inflation and the weakening of the rupiah against US against unemployment, poverty. (2). Obtain some alternative ways to overcome inflation and weakening of rupiah exchange rate against US dollar in maintaining stability of welfare of SMEs in Lombok region. (3) To evaluate the marketing system used by MSMEs (4) To know the obstacles faced by MSMEs (5) To know the related sectors in supporting the success of UMKM. Method of research used descriptive and qualitative method, with literary study approach, Data Collection, using participant observation and in-depth interviews. Data Validity, with triangulation method of source, method and time. The results show that the SME sector has contributed to the economic and development of Indonesia. There are several factors that challenge the development of SMEs.